2006
DOI: 10.1002/fut.20248
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the relationship between hedge ratio and hedging horizon using wavelet analysis

Abstract: In this article, optimal hedge ratios are estimated for different hedging horizons for 23 different futures contracts using wavelet analysis. The wavelet analysis is chosen to avoid the sample reduction problem faced by the conventional methods when applied to non-overlapping return series. Hedging performance comparisons between the wavelet hedge ratio and error-correction (EC) hedge ratio indicate that the latter performs better for more contracts for shorter hedging horizons. However, the performance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 21 publications
(29 reference statements)
7
73
1
Order By: Relevance
“…Table 2 shows the optimal futures hedge ratio for each objective function at different time-horizons in the case of heating oil. Considering first the minimum-variance hedging objective, the average hedge ratio is found to increase for longer hedging horizon, in keeping with previous findings (Lien & Shrestha, 2007;In & Kim, 2006). In fact, for a hedger with a horizon greater than 6 days, the optimal hedge ratio is greater than the naive ratio (one), suggesting that the hedging strategy requires that the hedger sells more than one futures contract for each short position held.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Table 2 shows the optimal futures hedge ratio for each objective function at different time-horizons in the case of heating oil. Considering first the minimum-variance hedging objective, the average hedge ratio is found to increase for longer hedging horizon, in keeping with previous findings (Lien & Shrestha, 2007;In & Kim, 2006). In fact, for a hedger with a horizon greater than 6 days, the optimal hedge ratio is greater than the naive ratio (one), suggesting that the hedging strategy requires that the hedger sells more than one futures contract for each short position held.…”
Section: Resultssupporting
confidence: 71%
“…3 Applying a minimum-variance framework, In & Kim (2006) demonstrated that S&P index hedgers achieve greater effectiveness at longer horizons. Examining a wide range of futures contracts, Lien & Shrestha (2007) showed both increased hedge ratios and out-of-sample effectiveness in the case of a minimumvariance hedger for increasing horizon. Finally, Conlon & Cotter (2012) applied a minimum-variance framework to introduce a dynamic time and horizon dependent futures hedge ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between different hedging preferences are examined, with speculative hedging strategies resulting for hedgers with low risk aversion, long time horizons and non-zero expected returns. The insights obtained complement those found in previous studies focused on a simple horizon dependent minimum-variance hedging strategy (Lien & Shrestha, 2007;In & Kim, 2006). Finally, given the evidence of diverse hedging strategies among real firms we assess the hedging performance achieved by hedgers with differing preferences.…”
supporting
confidence: 55%
“…Further details on the application of wavelets to financial research can be found in Gençay et al (2001). 7 Further, Fernandez (2008) and Lien & Shrestha (2007) applied wavelet decomposition to minimumvariance futures hedging, demonstrating improved hedging performance for investors with long time horizons.…”
mentioning
confidence: 99%
“…However, most papers report a positive relationship between hedge horizon and hedging effectiveness (Chen et al, 2004, Lien andShrestha, 2007). A variety of methods have been used to calculate hedges over longer time horizons.…”
Section: Introductionmentioning
confidence: 99%